Peranan Banquet Event Order Dalam Meningkatkan Jumlah Tamu Pada Banquet Section Di Jogjakarta Plaza Hotel - Eri Mulyono, Ani Wijayanti dan Yulianto (Universitas Bina Sarana Informatika, 2013)
Now hotels in Yogyakarta occupancy is not just for recreation guests only, guests who attended the meeting were also joined staying at the hotel who hold such meeting and in charge of the event is a banquet, and the author will discuss about the banquet section in Jogjakarta Plaza Hotel is located in road Affandi-Gejayan, Complex Colombo, Sleman, Yogyakarta. Banquet section can be regarded as part of the service to people who hold meetings or other events in hotel with manual or guidelines B.E.O (Banquet Event Order), in addition to the duties and responsibilities of banquet staff and the equipment used is important to note because can support the performance of the employees. B.E.O (Banquet Event Order) indirectly represents the work order from the marketing to the banquet section and important for all departament. Keywords : The Role of Banquet Event Order, Banquet Section